Molecular Prevalence and Haematology of Tropical Theileriosis in Cholistani Cattle from Nomadic Herds of the Cholistan Desert, Pakistan - Saeed, Zaka; Iqbal, Furhan; Hussain, Mureed; Shaikh, Rehan Sadiq; Farooq, Umer; Akbar, Atif; Aktas, Munir (Kafkas Univ, Veteriner Fakultesi Dergisi, 2016)
This is the first report on tropical theileriosis in Cholistani cattle, with the aim of 1) assessing the reliability of PCR as a tool for diagnosis of the early/carrier state; 2) determining the prevalence of theileriosis; and 3) comparing haematological profiles of parasite-positive and parasite-negative cattle. A total of 264 cattle (142 female and 122 male; 127 adult and 137 young) were examined for tropical theileriosis through clinical examination, stained smear screening, and polymerase chain recation. No cattle showed clinical signs of the disease. Of the diagnostic tests, PCR was more sensitive for detection of the early/carrier state of theileriosis (19.3%) compared to stained thin blood smear examination (1.9%). Female (24.6%) and young animals (23.4%) showed higher prevalence than males and adults, but not significant (P>0.05). Prevalence of the disease (51.6%) was significantly higher (P<0.05) in summer. Haematological indices were not significantly different in parasite-positive compared to parasite-negative cattle, except for total protein and creatinine which were significantly higher in infected animals. The study revealed a substantial prevalence of tropical theileriosis in Cholistani cattle. Nevertheless, their adaptation to the climate and their potential for tick and disease resistance may reflect in the absence of clinical signs and in normal haematological indices.
Pakistan’ın cholistan çölünde başıboş dolaşan cholistan sığırlarında tropikal theileriosisin prevalansı ve kan değerleri
Keywords: Theileria annulata; Cattle; PCR; Pakistan